Race, Apology, and Public Memory at Maryland’s Hospital for the ’Negro’ Insane - Stuckey, Zosha (Disability Studies Quarterly, 2017)
To respond to a recent demand of the ACLU of Maryland, and to augment theories from Disability Incarcerated (2014) about the convergence of race, disability, and due process (or lack thereof), this essay analyzes the extent to which racism informed the creation of Maryland's Hospital for the 'Negro' Insane (Crownsville Hospital). In order to understand the extent of racism in Crownsville's earlier years, I will take into account 14 categories within conditions of confinement from 1921-1928 and compare them to the nearby, white asylum. Ultimately, the hospital joins the ranks of separate and unequal (Plessy vs. Ferguson) institutions founded alongside a rhetoric of fear that the Baltimore Sun daily paper deemed "a Black invasion" of the city of Baltimore. Even more, I add to public memory of this racialized space invoking the rhetorical frame, as Kendall Phillips advises, of responsibility and apology (versus absolution) within the context of present-day racial justice movements.